2006
DOI: 10.1007/s11259-005-3176-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional Prevalence of Helminth Infections in Cattle on Traditional, Small-scale and Large-scale Dairy Farms in Iringa District, Tanzania

Abstract: A cross-sectional study was carried out to determine the prevalence of gastrointestinal (GI) nematodes and flukes (Fasciola and amphistomes) infection in communally grazed traditional cattle, zero-grazed small-scale dairy cattle and intensively grazed large-scale dairy cattle through examination of helminth eggs in faeces. Results indicated that the type of management, especially the grazing habit, has a significant influence on the prevalence and intensity of GI nematodes and flukes. The prevalence of GI nema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
54
4
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 16 publications
(20 reference statements)
24
54
4
3
Order By: Relevance
“…Accordingly higher prevalence was recorded in females (47.5%) than in males (35.3%) which may be due to differences in exposure to infection as a result of the variation in stocking density (sex ratio), the present study agrees the previous reports of Degefu et al [19] but contradict the result of Keyyu et al and Pfukenyi et al [11,12].…”
Section: Discussionsupporting
confidence: 79%
“…Accordingly higher prevalence was recorded in females (47.5%) than in males (35.3%) which may be due to differences in exposure to infection as a result of the variation in stocking density (sex ratio), the present study agrees the previous reports of Degefu et al [19] but contradict the result of Keyyu et al and Pfukenyi et al [11,12].…”
Section: Discussionsupporting
confidence: 79%
“…This finding agrees with the reports of Keyyu et al (2006) and Kabaka et al (2013). This might be due to the fact that extensively managed cattle have more access to contaminated pasture.…”
Section: Helminth Infection and Management Systemsupporting
confidence: 92%
“…Our findings that animals under semi-extensive system had more egg counts than those kept under intensive management system agree with that of Keyyu et al 22 who reported that management practices especially grazing habitat has a significant influence on faecal egg counts in cattle infected with gastro intestinal nematodes. On the other hand, the number of trichostrongyle eggs in our study was lower in governmental farms than that of small-scale private farms.…”
supporting
confidence: 92%